2018
DOI: 10.1007/s11270-018-3909-8
|View full text |Cite
|
Sign up to set email alerts
|

Greywater Characteristics, Treatment Systems, Reuse Strategies and User Perception—a Review

Abstract: This paper presents a literature review of the quality of greywater generated in different, especially developing, countries, constituents found in greywater, some treatment systems, natural materials for treatment, some reuse strategies and public perception regarding greywater reuse. The review shows that generation rates are mostly influenced by lifestyle, types of fixtures used and climatic conditions. Contaminants found in greywater are largely associated with the type of detergent used and influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
102
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(156 citation statements)
references
References 81 publications
18
102
1
12
Order By: Relevance
“…This is confirmed by the reported diffusion coefficients of 30.85 10 −8 cm 2 s −1 , 27.89 10 −8 cm 2 s −1 , 22.29 10 −8 cm 2 s −1 , 20.40 10 −8 cm 2 s −1 and 19.22 10 −8 cm 2 s −1 for Na + , K + , Ca 2+ , Mg 2+ and H + , respectively, when a CEM is used as separator . Conversely, it has been reported that greywater contains surfactants that are anionic in their majority, avoiding competition with protons for the functional groups in CEMs and pH splitting. Another important aspect is that the acetate used as a carbon source in the MFCs of this study is a simple substrate that does not favour fermentative processes, unlike glucose or lactose that produce volatile fatty acids, diminishing the pH in the anolyte to 6.5–5.6, as has been reported in other works …”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…This is confirmed by the reported diffusion coefficients of 30.85 10 −8 cm 2 s −1 , 27.89 10 −8 cm 2 s −1 , 22.29 10 −8 cm 2 s −1 , 20.40 10 −8 cm 2 s −1 and 19.22 10 −8 cm 2 s −1 for Na + , K + , Ca 2+ , Mg 2+ and H + , respectively, when a CEM is used as separator . Conversely, it has been reported that greywater contains surfactants that are anionic in their majority, avoiding competition with protons for the functional groups in CEMs and pH splitting. Another important aspect is that the acetate used as a carbon source in the MFCs of this study is a simple substrate that does not favour fermentative processes, unlike glucose or lactose that produce volatile fatty acids, diminishing the pH in the anolyte to 6.5–5.6, as has been reported in other works …”
Section: Resultsmentioning
confidence: 69%
“…This wastewater is divided into blackwater, which come from toilets, and greywater, which come from kitchens, washing machines, showers, baths and hand basins . The greywater is of variable composition depending on lifestyle, geographical region and the activities of the occupants, but generally contains easily biodegradable organic matter, nutrients such as nitrogen and phosphorus, and high levels of dissolved oxygen 5.0–6.1 mg L −1 , and is alkaline pH (8) due to laundry activities . It has been reported that greywater represents c .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment kind was ascertained to have a meaningful impact on the quality of the treated GW [20]. Oteng-Peprah et al (2018) resulted that among the traditional treatment technologies, filtration techniques look feasible and have the potential of integration with other methods to obtain target specific treatment [21]. Opher et al (2017) used an analytical hierarchy process (AHP) to assess the effects of four methods of water reuse on three related stakeholders including public, community, and consumer groups [22].…”
Section: Introductionmentioning
confidence: 99%